Synthesis of imidazole derivatives in the last 5 years: An update - Devi Mayanglambam Maneeta; Devi Keisham Subharani; Singh Okram Mukherjee; Singh Thokchom Prasanta (Heterocyclic Communications, 2024)
Imidazole and its derivatives possess remarkable versatility, finding applications in medicine, synthetic chemistry, and industry. This review explores the latest advancements observed over the last few years (2018–2022), focusing on diverse multicomponent reactions conducted under different conditions. It highlights the role of catalysts and diverse conditions, optimizing synthetic efficiency. The review offers concise insights into emerging trends, making it a valuable resource for researchers and practitioners seeking greener and more efficient imidazole synthesis.